Iron‐rich olivine in the unequilibrated ordinary chondrite, MET 00526: Earliest stages of formation. (12th January 2021) - Dobrică, Elena; Brearley, Adrian J.
Abstract: In order to understand the effects of the earliest stages of hydrothermal alteration and fluid‐assisted metamorphism on the matrices of unequilibrated ordinary chondrites (UOCs), we have investigated the fine‐grained matrix of MET 00526 (L3.05) using multiple electron microscope techniques. Iron‐rich olivines (Fa50‐100 ) are present in all four representative fine‐grained matrix regions analyzed in this study. This study shows for the first time the occurrence of FeO‐rich olivines in distinct submicron veins that crosscut regions of matrix consisting of amorphous silicates and phyllosilicates, providing evidence for elemental mass transport in a hydrothermal fluid. Our detailed transmission electron microscopy study reinforces the idea that FeO‐rich olivines are formed on asteroidal parent bodies by the interaction between a hydrothermal fluid and the pristine solar nebular materials that may be the product of condensation processes in the protoplanetary disk, that is, amorphous silicates. We propose that the FeO‐rich olivines currently observed in MET 00526 matrix are the products of three possible reaction mechanisms, (1) replacement of amorphous silicates, (2) precipitation from an SiO‐rich fluid, and (3) replacement of phyllosilicates; all these mechanisms take place in the presence of an iron‐rich fluid. The chemical evolution of the hydrothermal fluid could trigger the formation of either fayalite or phyllosilicates depending on the Si/Fe ratios. A low Si/Fe ratio is required to form FeO‐rich olivines, rather than phyllosilicates, which form at high Si/Fe ratio. Although MET 00526 records the effects of secondary alteration processes, its fine‐grained matrix still preserves some evidence of its pristine, solar nebular characteristics.